High prevalence of overuse injury among iron-distance triathletes - Andersen, C. A.; Clarsen, B.; Johansen, T. V. (British Journal of Sports Medicine, 2013)
Background: Triathlon is an increasingly popular sport at both the elite and the recreational level. However, there have been few high-quality studies of injuries and illnesses among triathletes.